Illocutionary Acts Found In Barack Obama’s Interview With Jimmy Kimmel Live Show - Putu Asrini; Luh Putu Laksminy; I Nyoman Tri Ediwan (Denpasar Institute, 2025)
Pragmatics is a branch of linguistics that examines how meaning is shaped through language use within specific contexts involving speakers and listeners. Central to this field is speech act theory, which explains how utterances perform actions and create social meaning. This study analyzes the types and functions of illocutionary acts used in an interview between Jimmy Fallon and former U.S. President Barack Obama, illustrating how pragmatic strategies operate in media interaction. Employing a descriptive qualitative approach, the analysis is based on Searle’s (1976) classification of illocutionary acts. Data were gathered through documentation and note-taking. The findings reveal three dominant illocutionary acts: representatives, directives, and expressives. Representatives convey beliefs or statements of fact, directives seek to influence the listener through questions or suggestions, and expressives communicate emotions or evaluations. Overall, the study shows how these illocutionary acts contribute to communicative intent, reflect interpersonal dynamics, and highlight the interactional styles of both interviewer and interviewee.